Differential Disclosure Experiences Amongst Sexual Victimization Survivors: Exploration of Alcohol Use, Sexual Risk Behaviors, and Mental Health Outcomes - Vittone, Ange (My University, 2025)
Sexual victimization is a pervasive issue that significantly impacts the physical, mental, and emotional well-being of survivors. This study investigates how disclosure experience differences influence variability in negative post-victimization outcomes - specifically alcohol use, sexual risk behaviors, and mental health symptoms- amongst cisgender women survivors of sexual victimization (N=347), aged 21-30. Through secondary data analysis, we assessed disclosure characteristics, including disclosure status (completed or non-disclosure), recipient type (informal vs. formal), and perceived helpfulness across assault types - and their relationship to post-victimization negative outcomes. Findings reveal that, contrary to prior literature, survivors who do not disclose their victimization exhibited lower levels of sexual risk-taking in comparison to survivors who did disclose their victimization. Notably, when examining only the type of disclosure recipient, survivors of adult/adolescent sexual assault (ASA) who disclosed exclusively to formal recipients (e.g., medical professionals, law enforcement) exhibited significantly higher mental health symptoms, compared to those who experienced other assault types or disclosed to different recipient types. However, when factoring in perceived helpfulness of their disclosure, survivors from all assault types who felt their disclosure was helpful reported significantly lower alcohol use and risk, particularly when disclosing exclusively to formal recipients. These findings highlight the nuanced impact of disclosure on recovery experiences and underscore the need for improved support mechanisms for survivors. Insights gained are essential for future research and tailored interventions targeting victimization populations.
Thesis (Master's)--University of Washington, 2025
Keywords: Alcohol consumption; Disclosure; Mental health; post-assault outcomes; Sexual risk behaviors; Sexual victimization; Clinical psychology; Mental health; Psychology